Peace and tenderness: An analysis on chinese female contemporary composer Leilei Tian’s works - Liu Mingqing; Lee Chie Tsang Isaiah (Francis Academic, 2023)
Tian Leilei is a renowned contemporary composer from China, recognized for her significant contributions to the field of music composition. Notably, she achieved the distinction of being the first Chinese recipient of the prestigious Besancon composition competition, where she was awarded the esteemed 1st prize. The artistic creations of this individual are widely recognized for their adept utilization of compositional techniques and distinctive aesthetic. The artistic endeavors of the individual in question have garnered significant attention and acclaim on a global scale. This article aims to explore Tian's composition style by briefly analyzing four pieces of her work from different periods of time.